2015
DOI: 10.3329/jemc.v5i2.23382
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ramadan Fasting on Anthropometric Measures and Metabolic Profiles among Type 2 Diabetic Subjects

Abstract: 54.7 ± 11.55 (range 35-80) years and mean duration of diabetes was 5.5 ± 5.2 years (range 9 months-18 years). In this study mean weight of the patients decreased significantly from 60.5 ± 12.6 kg to 58.5 ± 11.3 kg (p<0.001). Blood pressure reduced but not significantly. Fasting blood glucose showed significant reduction from 10.7 ± 4.2 to 8.9 ± 3.7 mmol/L (p=0.002) Fasting in Ramadan is one of the five pillars of Islam. During this month all adult Muslims abstain not only from eating, drinking, smoking and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
(20 reference statements)
1
1
0
3
Order By: Relevance
“…Changes in glucose level and lipid profile among various investigations may be because of variety in amount and type of food consumed in Ramadan, physical action, or medical prescriptions. 18,38 The current study results are in agreement with the investigation conducted in Algeria and revealed that there was a significant statistically decrease in all cholesterol, triglycerides, LDL and HbA1c. 34 Similarly, in Tunis, there was a significant decrease in fasting blood glucose, cholesterol, LDL and HDL while there was no significant difference in triglyceride.…”
Section: Discussionsupporting
confidence: 92%
“…Changes in glucose level and lipid profile among various investigations may be because of variety in amount and type of food consumed in Ramadan, physical action, or medical prescriptions. 18,38 The current study results are in agreement with the investigation conducted in Algeria and revealed that there was a significant statistically decrease in all cholesterol, triglycerides, LDL and HbA1c. 34 Similarly, in Tunis, there was a significant decrease in fasting blood glucose, cholesterol, LDL and HDL while there was no significant difference in triglyceride.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have been conducted on the effects of fasting, the majority of which are related to patients who have diabetes and management of their disease (3)(4)(5)(6)(7)(8)(9)(10). However, other studies have been conducted on non-diabetes patients and healthy subjects (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Puasa pada bulan Ramadan merupakan salah satu ibadah yang wajib dilakukan oleh setiap muslim dewasa/baligh yang sehat dan kewajiban ini dapat gugur bagi orang pada kondisi tertentu, salah satunya dalam keadaan sakit. Namun sebagian besar penderita DM tetap memutuskan untuk menjalankan ibadah puasa karena tidak merasakan sakit 7 Puasa dapat mempengaruhi ritme homeostatik tubuh, dan bagi pasien dengan penyakit kronis yang menggunakan obat secara terus menerus seperti pasien DM, puasa menyebabkan berubahnya pola pengobatan 6 . Puasa Ramadan bagi penderita DM menjadi suatu tantangan bagi pasien itu sendiri dan tenaga kesehatan karena adanya risiko yang timbul akibat perubahan asupan nutrisi dan perubahan penggunaan obat 8,9 Pada bulan Ramadhan, cenderung terjadi perubahan waktu makan.…”
Section: Pendahuluanunclassified